Quantifying the vegetation restoration mechanism of ecological projects on the Qingzang Plateau - Yang Chen; Guihua Yi; Xuan Zhu; Xiaobing Zhou; Tingbin Zhang; Bin Yang; Jingji Li; Xian Liu; Xianglong Ma (International Journal of Digital Earth)
Understanding how ecological restoration projects (ERPs) enhance vegetation recovery is crucial for sustainable ecological management. Previous studies have often examined single projects, overlooking the complexity of concurrent ERPs. We established an Ecological Engineering Composite Index (EECI), integrating ERP type, implementation intensity, and duration, to comprehensively evaluate their holistic impact on vegetation dynamics across the Qingzang Plateau (QP). Using geographic detector and structural equation modeling (SEM), we identified primary drivers of vegetation restoration and examined their interactions. From 2000 to 2020, the QP’s exhibited a significant greening, with kNDVI increasing by 0.023 per decade. The Natural Forest Conservation Program exerted the strongest influence, followed by the Yangtze River Basin Shelter Forest System Construction Project. Geodetector and SEM analyses identified precipitation, EECI, and solar radiation as main drivers of vegetation change, with notable synergistic interactions among climate, engineering, and terrain. While climate factors dominated, the cumulative impact of multiple ERPs quantified by EECI was decisive for large-scale recovery. Regions with higher EECI consistently exhibited greater kNDVI gains, confirming that coordinated, intensive restoration yields the greatest ecological benefits. By quantifying the integrated effects of multiple ERPs, this study provides guidance for optimizing ecological policy and sustaining long-term ra2c: vegetation restoration on the QP.HIGHLIGHTS kNDVI on the Qingzang Plateau rises by 0.023/10a, and in project zones by 0.029/10aThe Natural Forest Conservation Program shows the highest vegetation recoveryHigher ecological engineering composite index leads to better vegetation recovery